Anthropological Foundations of Developing the Affirmative Thinking in the Children and it’s Educational Implications from the Islam’s Viewpoint - Shirin Rashidi; Atieh sadat Alavi (علوم تربیتی از دیدگاه اسلام, 2022)
This article has been written with the aim of explaining anthropological foundations of developing the affirmative thinking in the children and it’s educational implications from the Islam’s viewpoint. For this purpose, the authors has tried to introducing the anthropological foundations of this thinking and it’s objectives from the Islam’s viewpoint and the methods of developing this thinking, in addition to explaining the conception of affirmative thinking. This research from the viewpoint of its general approach is qualitative and deductive, from the viewpoint of its method is analytical – inferential, and from the viewpoint of its method of data gathering is attributed to library. Its statistical society contains Islamic texts and the works of  Moslim’s thinkers. On the base of the findings of this research, anthropological foundations of development of affirmative thinking contains nine parts: two dimensional of the human existence, servitude of the human being in the eyes of God, authority in the human being, sociality, self friendship, perfection seeking,  introduction being the worldly life for the futurity life, and eventually the difference between the human beings from the viewpoint of their potentialities. The objectives of affirmative thinking from the Islam’s viewpoint are: developing the jubilation and satisfaction in the life, believing in transience of the problems, trust in the God, and the power of the application of oppositional and effective styles in the face of problems. And eventually the methods of developing affirmative thinking in the children from the Islam’s viewpoint are: encouraging the development and extension the affirmative affections in the children, forgiveness, remembering and praising the abundances, patience, and attending the children to the futurity life.